EuroGuiDerm Guideline on the systemic treatment of Psoriasis vulgaris – Part 2: specific clinical and comorbid situations. (5th February 2021) - Nast, A.; Smith, C.; Spuls, P.I.; Avila Valle, G.; Bata‐Csörgö, Z.; Boonen, H.; De Jong, E.; Garcia‐Doval, I.; Gisondi, P.; Kaur‐Knudsen, D.; Mahil, S.; Mälkönen, T.; et al.
Abstract: This evidence‐ and consensus‐based guideline on the treatment of psoriasis vulgaris was developed following the EuroGuiDerm Guideline and Consensus Statement Development Manual. The second part of the guideline provides guidance for specific clinical and comorbid situations such as treating psoriasis vulgaris patient with concomitant psoriatic arthritis, concomitant inflammatory bowel disease, a history of malignancies or a history of depression or suicidal ideation. It further holds recommendations for concomitant diabetes, viral hepatitis, disease affecting the heart or the kidneys as well as concomitant neurological disease. Advice on how to screen for tuberculosis and recommendations on how to manage patients with a positive tuberculosis test result are given. It further covers treatment for pregnant women or patients with a wish for a child in the near future. Information on vaccination, immunogenicity and systemic treatment during the COVID‐19 pandemic is also provided.